Penggunaan E-learning Berbasis Moodle bagi KKG Sekolah Dasar di Kecamatan Lengkong Kota Bandung - Inggriyani, Feby; Fazriyah, Nurul; Purbasari, Ayi (Jurnal SOLMA, 2019)
Abstract Learning conducted by KKG in Lengkong District, Bandung City has not used digital-based technology. Whereas the application of learning towards the 21st century must be digital based and learning is a benchmark as a means of improving the quality of student learning outcomes. Thus, understanding and skills are needed for KKG to solve partner problems. The purpose of community service activities is to provide knowledge about the use of e-learning-based technology for the KKG District of Lengkong, Bandung. This activity method is carried out with workshops through lecture, question and answer, discussion, training, and assignment techniques. Provision of material begins with the introduction of e-learning and the practice of using moodle in learning. The material ended by giving an independent task for each participant to create and develop their own e-learning. Based on the results of the activity, all participants were very enthusiastic and participated in each session until the end. This activity was carried out successfully, smoothly and according to plan and had an impact on increasing the understanding of KKG's knowledge and skills in the use of moodle-based e-learning. It is hoped that through this workhop, KKG can improve the quality of learning by using moodle-based learning technology to foster learning motivation and support student learning outcomes. Keywords: e-learning, elementary school KKG, moodle